2017
DOI: 10.1097/md.0000000000008330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polydeoxyribonucleotide injection on pes anserine bursitis

Abstract: Rationale:Pes anserine (PA) bursitis is an inflammatory condition of the medial knee. The PA bursa becomes more painful when infected, damaged, or irritated. Although various treatment options have been attempted to treat PA bursitis, optimal treatments are still debated. This study aims to investigate the effect of polydeoxyribonucleotide (PDRN) injection on reducing pain and inflammation in a patient presenting with PA bursitis.Patient concerns:A 50-year-old female patient was admitted to our pain clinic wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Furthermore, only 3 studies used PDRN extracted from Acipenser sinensis (As-PDRN). Sturgeons ( A. sinensis ), a species with the fastest growth rate among the three sources, is a novel PDRN extraction source used by Veritas in Italy [ 12 , 13 , 14 , 15 ]. Pharmaresearch Product (Pangyo, Korea), Mastelli Srl (San Remo, Italy), and Veritas (Brescia, Italy) exclusively provide Om-PDRN, PDRN extracted from O. keta (Ok-PDRN), and As-PDRN ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, only 3 studies used PDRN extracted from Acipenser sinensis (As-PDRN). Sturgeons ( A. sinensis ), a species with the fastest growth rate among the three sources, is a novel PDRN extraction source used by Veritas in Italy [ 12 , 13 , 14 , 15 ]. Pharmaresearch Product (Pangyo, Korea), Mastelli Srl (San Remo, Italy), and Veritas (Brescia, Italy) exclusively provide Om-PDRN, PDRN extracted from O. keta (Ok-PDRN), and As-PDRN ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 , 12 ] PDRN repairs and regenerates cellular damage by interacting with A2 purinergic receptor and stimulating the production of vascular endothelial growth factors. [ 11 ] PDRN has recently found wide application throughout the medical field: [ 13 ] not only in DM ulcer and cosmetics, but also in musculoskeletal areas. Even though PDRN does not seem to have an equivalent persistence effect compared to triamcinolone, considering the systemic side effects of steroids, particularly in patients with diabetes or metabolic syndrome, it appears that PDRN is worthwhile as an option for the treatment of hemiplegic shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“…Even though PDRN does not seem to have an equivalent persistence effect compared to triamcinolone, considering the systemic side effects of steroids, particularly in patients with diabetes or metabolic syndrome, it appears that PDRN is worthwhile as an option for the treatment of hemiplegic shoulder pain. [ 14 ] Mun et al [ 13 ] reported the effectiveness of PDRN injection on pes anserinus bursitis. Lim et al [ 11 ] reported the effectiveness of PDRN injection in posterior tibial tendon dysfunction patients undergoing ankle syndesmotic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided PA bursa injection of PDRN significantly reduced pain at the 2-week follow-up visit, and complete functional recovery was achieved at the 8-month follow-up examination. 75 Numerous studies have confirmed the efficacy of PDRN in reducing pain and symptoms of inflammation in tendinopathy, a musculoskeletal disorder for which an optimal treatment has not yet been established. 76 Glucocorticoids represent the most common treatment choice for this pathology.…”
Section: Pdrn and The Regulation Of Inflammation: Clinical Endpointsmentioning
confidence: 99%